FLAD1‐associated multiple acyl‐CoA dehydrogenase deficiency identified by newborn screening. Issue 9 (8th August 2019) - Muru, Kai; Reinson, Karit; Künnapas, Kadi; Lilleväli, Hardo; Nochi, Zahra; Mosegaard, Signe; Pajusalu, Sander; Olsen, Rikke K. J.; Õunap, Katrin
Abstract: Background: Multiple acyl‐CoA dehydrogenase deficiency (MADD), also known as glutaric aciduria type II, is a mitochondrial fatty acid oxidation disorder caused by variants in ETFA, ETFB, and ETFDH . Recently, riboflavin transporter genes and the mitochondrial FAD transporter gene have also been associated with MADD‐like phenotype. Methods: We present a case of MADD identified by newborn biochemical screening in a full‐term infant suggestive of both medium‐chain acyl‐CoA dehydrogenase deficiency and MADD. Urine organic acid GC/MS analysis was also concerning for both disorders. However, panel sequencing of ETFA, ETFB, ETFDH, and ACADM was unrevealing. Ultimately, a variant in the FAD synthase gene, FLAD1 was found explaining the clinical presentation. Results: Exome sequencing identified compound heterozygous variants in FLAD1: NM_025207.4: c.[442C>T];[1588C>T], p.[Arg148*];[Arg530Cys]. The protein damaging effects were confirmed by Western blot. The patient remained asymptomatic and there was no clinical decompensation during the first year of life. Plasma acylcarnitine and urinary organic acid analyses normalized without any treatment. Riboflavin supplementation was started at 15 months. Conclusion: Newborn screening, designed to screen for specific treatable congenital metabolic diseases, may also lead to the diagnosis of additional, very rare metabolic disorders such as FLAD1 deficiency. The case further illustrates that even milder forms of FLAD1 deficiency are detectable in the asymptomatic state by newborn screening. Abstract : Newborn screening is designed to screen for specific treatable congenital metabolic diseases, though due to the use of tandem MS technology has the potential to also detect very rare metabolic disorders that are not the intended targets of the newborn screening assay. One example of such a disorder is MADD, which may be caused by biallelic FLAD1 variants. This is an important diagnosis to make in the newborn period, as it might be riboflavin‐responsive and treatable. The present case therefore illustrates that FLAD1 genotypes associated with a milder and late‐onset disease can be detected and potentially prevented by early newborn screening.